Prospects and challenges for the recovery of 2‐butanol produced by vacuum fermentation – a techno‐economic analysis. Issue 7 (29th March 2017) - Pereira, Joana P. C.; Lopez‐Gomez, Gustavo; Reyes, Noelia G.; van der Wielen, Luuk A. M.; Straathof, Adrie J. J.
Abstract: The conceptual design of a bio‐based process for 2‐butanol production is presented for the first time. Considering a hypothetical efficient producing strain, a vacuum fermentation is proposed to alleviate product toxicity, but the main challenge is the energy‐efficient product recovery from the vapor. Three downstream scenarios were examined for this purpose: 1) multi‐stage vapor recompression; 2) temperature swing adsorption; and 3) vapor absorption. The processes were simulated using Aspen Plus, considering a production capacity of 101 kton/yr. Process optimization was performed targeting the minimum selling price of 2‐butanol. The feasibility of the different configurations was analyzed based on the global energy requirements and capital expenditure. The use of integrated adsorption and absorption minimized the energy duty required for azeotrope purification, which represents 11% of the total operational expenditure in Scenario 1. The minimum selling price of 2‐butanol as commodity chemical was estimated as 1.05 /kg, 1.21 /kg, and 1.03 /kg regarding the fermentation integrated with downstream scenarios 1), 2), and 3), respectively. Significant savings in 2‐butanol production could be achieved in the suggested integrated configurations if more efficient microbial strains were engineered, and more selective adsorption and absorption materials were found for product recovery. Abstract : The fermentative production of 2‐butanol, a potential biofuel and biocommodity chemical, has been largely overlooked so far. Since severe microbial inhibition occurs when 2‐butanol concentrations reach 1 wt.%, only integrated product removal can improve titer, yield, and productivity. In this study, the authors evaluate the prospects for 2‐butanol production by vacuum fermentation integrated with three distinct downstream scenarios for product recovery from the vapor‐phase. The use of integrated adsorption and absorption minimized the energy duty required for azeotrope purification, though the feedstock represents the most significant expenditure for all the scenarios. Overall, significant savings in 2‐butanol production can only be reached if more efficient microbial strains are used in a suitably integrated configuration, such as the ones suggested herein.